Light-Trapping Engineering for the Enhancements of Broadband and Spectra-Selective Photodetection by Self-Assembled Dielectric Microcavity Arrays - Ying, Anni (Nanoscale Res Lett, 2019)
Light manipulation has drawn great attention in photodetectors towards the specific applications with broadband or spectra-selective enhancement in photo-responsivity or conversion efficiency. In this work, a broadband light regulation was realized in photodetectors with the improved spectra-selective photo-responsivity by the optimally fabricated dielectric microcavity arrays (MCAs) on the top of devices. Both experimental and theoretical results reveal that the light absorption enhancement in the cavities is responsible for the improved sensitivity in the detectors, which originated from the light confinement of the whispering-gallery-mode (WGM) resonances and the subsequent photon coupling into active layer through the leaky modes of resonances. In addition, the absorption enhancements in specific wavelength regions were controllably accomplished by manipulating the resonance properties through varying the effective optical length of the cavities. Consequently, a responsivity enhancement up to 25% within the commonly used optical communication and sensing region (800 to 980 nm) was achieved in the MCA-decorated silicon positive-intrinsic-negative (PIN) devices compared with the control ones. This work well demonstrated that the leaky modes of WGM resonant dielectric cavity arrays can effectively improve the light trapping and thus responsivity in broadband or selective spectra for photodetection and will enable future exploration of their applications in other photoelectric conversion devices. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s11671-019-3023-x) contains supplementary material, which is available to authorized users.